Análisis a las auditorías realizadas por la contraloría distrital de Bogotá para conocimiento ciudadano (2022)
ABSTRACT The investigation focused on the citizen perception regarding the actions and results of the audits carried out by the public officials who work in the District Comptroller of Bogotá during the period 2017 to 2021, implementing a qualitative methodology with a descriptive analytical approach where they specify that Findings were recorded, in addition to looking for shortcomings in the presentation and information published by the aforementioned entity.